2021
DOI: 10.1002/jcp.30459
|View full text |Cite
|
Sign up to set email alerts
|

GPCR‐mediated YAP/TAZ inactivation in fibroblasts via EPAC1/2, RAP2C, and MAP4K7

Abstract: Yes-associated protein (YAP) and PDZ-binding motif (TAZ) have emerged as important regulators of pathologic fibroblast activation in fibrotic diseases. Agonism of Gαs-coupled G protein coupled receptors (GPCRs) provides an attractive approach to inhibit the nuclear localization and function of YAP and TAZ in fibroblasts that inhibits or reverses their pathological activation. Agonism of the dopamine D1 GPCR has proven effective in preclinical models of lung and liver fibrosis. However, the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…Consistent with this, we have observed prominent nuclear staining for YAP and TAZ in interstitial cells of IPF, but not control lungs (Liu et al, 2015). In previous work, we performed a GPCR-focused transcriptome screen to reveal the D1 dopamine receptor as a target to inactivate YAP/TAZ in lung fibroblasts, and we showed that an agonist of the D1 receptor, dihydrexidine, blocks YAP/TAZ nuclear localization, stimulates collagen degradation, and promotes lung fibrosis resolution in a 6 bleomycin lung injury model of fibrosis, consistent with the D1 receptor exclusively coupling to G alpha s (Choi et al, 2021;Diaz-Espinosa et al, 2020;Haak et al, 2019).…”
Section: Introductionsupporting
confidence: 52%
“…Consistent with this, we have observed prominent nuclear staining for YAP and TAZ in interstitial cells of IPF, but not control lungs (Liu et al, 2015). In previous work, we performed a GPCR-focused transcriptome screen to reveal the D1 dopamine receptor as a target to inactivate YAP/TAZ in lung fibroblasts, and we showed that an agonist of the D1 receptor, dihydrexidine, blocks YAP/TAZ nuclear localization, stimulates collagen degradation, and promotes lung fibrosis resolution in a 6 bleomycin lung injury model of fibrosis, consistent with the D1 receptor exclusively coupling to G alpha s (Choi et al, 2021;Diaz-Espinosa et al, 2020;Haak et al, 2019).…”
Section: Introductionsupporting
confidence: 52%
“…115 The Hippo pathway has been shown to be regulated by GPCR signalling. [116][117][118][119] For example, it was shown that GPCR ligands such as thrombin or lysophosphatidic acid (LPA) could activate YAP in fibroblasts and sensitize them to TGF-β1. 120 Additionally, sphingosine-1-phosphate (SIP) is a ligand of GPCR.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…LATS phosphorylation on S909 and T1079 is carried out by MST kinase (Chan et al, 2005; Hoa et al, 2016), but LATS can also be phosphorylated by MAP4 kinases (MAP4Ks) (Meng et al, 2015; Zheng et al, 2015) or STK25 kinase (Lim et al, 2019). In addition, both GPCR‐Rho‐F‐actin and cAMP‐PKA‐F‐actin (Choi et al, 2021; Yu et al, 2012) can activate the phosphorylation of LATS independently of MST, similar to the apparent effects of DMPCA on LATS. While it is tempting to speculate that a molecule in these actin pathways may be involved, the kinases or mechanisms responsible for DMPCA‐induced LATS phosphorylation remain under investigation.…”
Section: Discussionmentioning
confidence: 94%